2019
DOI: 10.29328/journal.apb.1001007
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on binding interactions of laccase-enzyme from Ganoderma weberianum with multiples ligand substrates with environmental impact

Abstract: Laccase catalyzes oxidation of lignin and aromatic compound with similar structure to this one. Their low substrate specifi city results on degradation of similar phenolic compounds. In this context, Molecular Docking was performed with different ligands suggesting potential biodegradation. Binding active-sites prediction of fungal laccase (access number uniprotkb: A0A166P2X0), from Ganoderma weberianum was performed using machine learning algorithm based on Deep Convolutional Neural Networks (DeepSite-CNNs ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…The antimicrobial trimethoprim showed an affinity of −6.1 kcal/mol and interacted hydrophobically with His124, which belongs to the conserved motif bound to CuII, Lys412, Met521 (CuIV), Leu410, Pro411 and Tyr95, and established hydrogen bonds with Met520 (CuIV) and Met126 (Figure 7D). The interaction of trimethoprim with CuIV (His479) was also described by Cárdenas-Moreno et al [44], who reported a binding energy of −6.5 kcal/mol, very close to our result.…”
Section: Molecular Docking and Ligand Preparationsupporting
confidence: 92%
“…The antimicrobial trimethoprim showed an affinity of −6.1 kcal/mol and interacted hydrophobically with His124, which belongs to the conserved motif bound to CuII, Lys412, Met521 (CuIV), Leu410, Pro411 and Tyr95, and established hydrogen bonds with Met520 (CuIV) and Met126 (Figure 7D). The interaction of trimethoprim with CuIV (His479) was also described by Cárdenas-Moreno et al [44], who reported a binding energy of −6.5 kcal/mol, very close to our result.…”
Section: Molecular Docking and Ligand Preparationsupporting
confidence: 92%
“…The root mean square deviation of the laccase-tetracycline interaction was 1.991. As lower values indicate higher similarity, it may be concluded that laccase can effectively bind to tetracycline [ 103 ].…”
Section: Effective Methods Of Tetracycline Removal From the Aquatic E...mentioning
confidence: 99%
“…3,45 For example, such regions were identified in a G. weberianum laccase toward benzidine, antibiotics, model dyes such as Remazol Brilliant Blue R and Intra, and specific synthetic substrates, such as 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic) acid (ABTS) and 2,6-dimethoxyphenol (DMF) by bioinformatic methods. 74 A similar approach was used to predict the interaction among Trametes maxima laccase, ABTS, DMF, or the dyes acid blue 62, 113, and 116. 7 The T. versicolor laccase has broad substrate specificity, thus biotransforming compounds such as phenols, monophenols, and multisubstituted derivatives, including chlorophenols, nitrophenols, and bisphenols.…”
Section: Oxidases Substratesmentioning
confidence: 99%
“…For many of these ligands, the active site regions involved in the interactions have also been characterized 3,45 . For example, such regions were identified in a G. weberianum laccase toward benzidine, antibiotics, model dyes such as Remazol Brilliant Blue R and Intra, and specific synthetic substrates, such as 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic) acid (ABTS) and 2,6‐dimethoxyphenol (DMF) by bioinformatic methods 74 . A similar approach was used to predict the interaction among Trametes maxima laccase, ABTS, DMF, or the dyes acid blue 62, 113, and 116 7 .…”
Section: Oxidasesmentioning
confidence: 99%